Commentary: Chronotopes, synchronization and formats. (January 2020) - Blommaert, Jan
Abstract: After a brief discussion of how the notion of chronotope enables us to address issues of context and contextualization in a more adequate way, this commentary turns to how, in the papers of this volume, two major themes emerge. One is about chronotope as a primarily moral notion; the other about chronotopic relations as forms of synchronization, where the latter can be understood as revolving around indexical vector reorientation towards 'formats' Highlights: The paper engages with substantive theoretical issues regarding contextualization. Discussion of special issue papers. Chronotopes, scales.